A Question Mark on Iron Deficiency in 185 Million People of Pakistan: Its Outcomes and Prevention - Anwaar Ahmed; Asif Ahmad; Nauman Khalid; Angel David; Mansoor Abdullah Sandhu; Muhammad Atif Randhawa; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2014)

Effects of steam-treated rice straw feeding on growth, digestibility, and plasma volatile fatty acids of goats under different housing systems - Naeem Muhammad; Rajput Nasir; Dong Li; Zhang Lili; Wang Tian (Tropical Animal Health and Production, 2014)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

Cystic hydatidosis in slaughtered goats from various municipal abattoirs in Oman - Fadya Al-Kitani; Senan Baqir; Muhammad Hammad Hussain; Derek Roberts (Tropical Animal Health and Production, 2014)

To cope or to sustain? Eroding long-term sustainability in an Indonesian coral reef fishery - Sebastian C. A. Ferse; Marion Glaser; Muhammad Neil; Kathleen Schwerdtner Máñez (Regional Environmental Change, 2014)

Phylogenetic analysis of STK gene family and Usp domain in maize - Ting Zhou; Mingxia Fan; Muhammad Irfan; He Wang; Dongxu Wang; Lin Wang; Chunyu Zhang; Lin Feng (Molecular Biology Reports, 2014)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

Mapping QTLs for Swimming Ability Related Traits in Cyprinus carpio L. - Muhammad Younis Laghari; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Naeem Tariq Narejo; Yongxin Liu; Shahid Mehboob; K. Al-Ghanim; Yan Zhang; Xiaowen Sun (Marine Biotechnology, 2014)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Effects of nitric oxide modulating activities on development of enteric nervous system mediated gut motility in chick embryo model - Hossein-Ali Arab; Samad Muhammadnejad; Seyed-Muhammad Faghihi; Hossein Hassanpour; Ahad Muhammadnejad (Journal of Biosciences, 2014)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

RETRACTED ARTICLE: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2014)

Exogenous proline and glycinebetaine mitigate cadmium stress in two genetically different spring wheat (Triticum aestivum L.) cultivars - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Muhammad Zulqurnain Haider; Uzma Kanwal; Muhammad Iqbal (Brazilian Journal of Botany, 2014)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Comparative Study of Trace Elements in Blood, Scalp Hair and Nails of Prostate Cancer Patients in Relation to Healthy Donors - Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2014)

Synthesis, spectroscopic characterization, electrochemical behavior and computational analysis of mixed diamine ligand gold(III) complexes: antiproliferative and in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; M. Monim-ul-Mehboob; Muhammad Altaf; Abdulaziz A. Al-Saadi; Mohammed I. M. Wazeer; Saleh Altuwaijri; Anvarhusein A. Isab (BioMetals, 2014)

Comparative cytological and transcriptomic analysis of pollen development in autotetraploid and diploid rice - Jinwen Wu; Muhammad Qasim Shahid; Haibin Guo; Wei Yin; Zhixiong Chen; Lan Wang; Xiangdong Liu; Yonggen Lu (Plant Reproduction, 2014)

Arthrobacter ginsengisoli sp. nov., isolated from soil of a ginseng field - Muhammad Zubair Siddiqi; Yeon-Ju Kim; Van-An Hoang; Muhammad Hanif Siddiqi; Md. Amdadul Huq; Deok-Chun Yang (Archives of Microbiology, 2014)

History and Origin of Russet Burbank (Netted Gem) a Sport of Burbank - Paul C. Bethke; Atef M. K. Nassar; Stan Kubow; Yves N. Leclerc; Xiu-Qing Li; Muhammad Haroon; Teresa Molen; John Bamberg; Max Martin; Danielle J. Donnelly (American Journal of Potato Research, 2014)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Flavonoids with antimicrobial activity from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad Sani Sallau; Aliyu Muhammad Musa; Dama James Habila; Sani Muhammad Yahaya (Natural Product Research, 2014)

A Spatial Multi-Criteria Analysis Approach for Locating Suitable Sites for Construction of Subsurface Dams in Northern Pakistan - Imran Ali Jamali; Ulla Mörtberg; Bo Olofsson; Muhammad Shafique (Water Resources Management, 2014)

Optical Properties of Some Novel 2,5-Disubstituted 1,3,4-Oxadiazole Derivatives and their Application as an Efficient Cell Staining Azo Dyes - Muhammad Saleem; Anser Ali; Bong Joo Park; Eun Ha Choi; Ki Hwan Lee (Journal of Fluorescence, 2014)

Spectroscopic Investigation, Effect of Solvent Polarity and Fluorescence Quenching of a New D-π-A Type Chalcone Derivative - Mehboobali Pannipara; Abdullah M. Asiri; Khalid A. Alamry; Muhammad N Arshad; Samy A. El-Daly (Journal of Fluorescence, 2014)

Rearing of Bactrocera zonata (Diptera: Tephritidae) for parasitoids production and managing techniques for fruit flies in mango orchards - S. M. M. Shah; Nazir Ahmad; Muhammad Sarwar; Muhammad Tofique (International Journal of Tropical Insect Science, 2014)

Identification of a homozygous splice site mutation in the dynein axonemal light chain 4 gene on 22q13.1 in a large consanguineous family from Pakistan with congenital mirror movement disorder - Iltaf Ahmed; Kirti Mittal; Taimoor I. Sheikh; Nasim Vasli; Muhammad Arshad Rafiq; Anna Mikhailov; Mehrnaz Ohadi; Huda Mahmood; Guy A. Rouleau; Attya Bhatti; Muhammad Ayub; Myriam Srour; et al. (Human Genetics, 2014)

Determination of heavy metal contents in water, sediments, and fish tissues of Shizothorax plagiostomus in river Panjkora at Lower Dir, Khyber Pakhtunkhwa, Pakistan - Kabir Ahmad; Azizullah Azizullah; Shama Shama; Muhammad Nasir Khan Khattak (Environmental Monitoring and Assessment, 2014)

Luteovirus: insights into pathogenicity - Muhammad Ali; Shahid Hameed; Muhammad Tahir (Archives of Virology, 2014)

Erratum to: The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

Modulation in growth, photosynthetic efficiency, activity of antioxidants and mineral ions by foliar application of glycinebetaine on pea (Pisum sativum L.) under salt stress - Nida Nusrat; Muhammad Shahbaz; Shagufta Perveen (Acta Physiologiae Plantarum, 2014)

Morpho-anatomical and physiological attributes for salt tolerance in sewan grass (Lasiurus scindicus Henr.) from Cholistan Desert, Pakistan - Nargis Naz; Tanzila Rafique; Mansoor Hameed; Muhammad Ashraf; Riffat Batool; Sana Fatima (Acta Physiologiae Plantarum, 2014)

Phytostabilization and Physicochemical Responses of Korean Ecotype Solanum nigrum L. to Cadmium Contamination - Abdur Rahim Khan; Ihsan Ullah; Abdul Latif Khan; Sung-Jun Hong; Muhammad Waqas; Gun-Seok Park; Yunyoung Kwak; JungBae Choi; Byung-Kwon Jung; Man Park; In-Jung Lee; Jae-Ho Shin (Water, Air, & Soil Pollution, 2014)

Effect of management practices and animal age on incidence of mastitis in Nili Ravi buffaloes - Tariq Ali; Abdur Rahman; Muhammand Subhan Qureshi; Muhammad Tariq Hussain; Muhammad Shauib Khan; Siraj Uddin; Muhammad Iqbal; Bo Han (Tropical Animal Health and Production, 2014)

Upgrade of egg quality through different heat-combating systems during high environmental temperature - Muhammad Safdar Anjum; Mansur Abdullah Sandhu; Nasir Mukhtar; Zia-ur Rahman (Tropical Animal Health and Production, 2014)

Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Polar Biology, 2014)

Comprehensive analysis of CCCH-type zinc finger gene family in citrus (Clementine mandarin) by genome-wide characterization - Shengrui Liu; Muhammad Rehman Gul Khan; Yongping Li; Jinzhi Zhang; Chungen Hu (Molecular Genetics and Genomics, 2014)

Synthesis and effect of substituent position on anti-inflammatory activity of 3-(halobenzyl)isocarbostyrils - Tariq Mahmood Babar; Muhammad Moazzam Naseer; Farukh Iftakhar Ali; Nasim Hasan Rama; Taibi Ben Hadda (Medicinal Chemistry Research, 2014)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

A high virulence and pathotype diversity of Puccinia striiformis f.sp. tritici at its centre of diversity, the Himalayan region of Pakistan - Sajid Ali; Marc Leconte; Hidayatur Rahman; Muhammad Shahab Saqib; Pierre Gladieux; Jérôme Enjalbert; Claude de Vallavieille-Pope (European Journal of Plant Pathology, 2014)

Water quality change in dam reservoir and shallow aquifer: analysis on trend, seasonal variability and data reduction - Shakhawat Chowdhury; Muhammad Al-Zahrani (Environmental Monitoring and Assessment, 2014)

Phytohormone-producing fungal endophytes and hardwood-derived biochar interact to ameliorate heavy metal stress in soybeans - Muhammad Waqas; Abdul Latif Khan; Sang-Mo Kang; Yoon-Ha Kim; In-Jung Lee (Biology and Fertility of Soils, 2014)

Identification of a distinct strain of cotton leaf curl Burewala virus - Malik Nawaz Shuja; Rob W. Briddon; Muhammad Tahir (Archives of Virology, 2014)

Effect of Ascorbic Acid on the Degradation of Cyanocobalamin and Hydroxocobalamin in Aqueous Solution: A Kinetic Study - Iqbal Ahmad; Kiran Qadeer; Saima Zahid; Muhammad Ali Sheraz; Tehmina Ismail; Waqar Hussain; Izhar Ahmad Ansari (AAPS PharmSciTech, 2014)

LlHSFA1, a novel heat stress transcription factor in lily (Lilium longiflorum), can interact with LlHSFA2 and enhance the thermotolerance of transgenic Arabidopsis thaliana - Benhe Gong; Jin Yi; Jian Wu; Juanjuan Sui; Muhammad Ali Khan; Ze Wu; Xionghui Zhong; Shanshan Seng; Junna He; Mingfang Yi (Plant Cell Reports, 2014)

Effect of emamectin benzoate on life history traits and relative fitness of Spodoptera litura (Lepidoptera: Noctuidae) - Syed Muhammad Zaka; Naeem Abbas; Sarfraz Ali Shad; Rizwan Mustafa Shah (Phytoparasitica, 2014)

Local Co-Delivery of Pancreatic Islets and Liposomal Clodronate Using Injectable Hydrogel to Prevent Acute Immune Reactions in a Type 1 Diabetes - Muhammad R. Haque; Dong Yun Lee; Cheol-Hee Ahn; Jee-Heon Jeong; Youngro Byun (Pharmaceutical Research, 2014)

Determinants of farmers’ choice of coping and adaptation measures to the drought hazard in northwest Balochistan, Pakistan - Muhammad Ashraf; Jayant K. Routray; Muhammad Saeed (Natural Hazards, 2014)

Expression patterns of miR-221 and its target Caspase-3 in different cancer cell lines - Sercan Ergun; Kaifee Arman; Ebru Temiz; İbrahim Bozgeyik; Önder Yumrutaş; Muhammad Safdar; Hasan Dağlı; Ahmet Arslan; Serdar Oztuzcu (Molecular Biology Reports, 2014)

Antibacterial Efficacy of Silver Nanoparticles Synthesized by a Green Method Using Bark Extract of Melia azedarach L - Ansar Mehmood; Ghulam Murtaza; Tariq Mahmood Bhatti; Muhammad Raffi; Rehana Kausar (Journal of Pharmaceutical Innovation, 2014)

Evaluation of drought and heat tolerance in wheat based on seedling traits and molecular analysis - Mahmoud Abo Elsaud El-Rawy; Muhammad Youssef (Journal of Crop Science and Biotechnology, 2014)

Cadmium-tolerant bacteria induce metal stress tolerance in cereals - Iftikhar Ahmad; Muhammad Javed Akhtar; Zahir Ahmad Zahir; Muhammad Naveed; Birgit Mitter; Angela Sessitsch (Environmental Science and Pollution Research, 2014)

Assessment of cadmium accumulation, toxicity, and tolerance in Brassicaceae and Fabaceae plants—implications for phytoremediation - Naser A. Anjum; Shahid Umar; Muhammad Iqbal (Environmental Science and Pollution Research, 2014)

Mercury accumulation in bats near hydroelectric reservoirs in Peninsular Malaysia - Khairunnisa Syaripuddin; Anjali Kumar; Kong-Wah Sing; Muhammad-Rasul Abdullah Halim; Muhammad-Nasir Nursyereen; John-James Wilson (Ecotoxicology, 2014)

Growth, water status, and leaf characteristics of Brassica carinata under drought and rehydration conditions - Azamal Husen; Muhammad Iqbal; Ibrahim M. Aref (Brazilian Journal of Botany, 2014)

Tracing Intracellular Localization and Chemical Forms of Copper in Elsholtzia splendens with Cluster Analysis - Tingting Liu; Feng Li; Xi Zhang; Hai Zhang; Dechao Duan; Chaofeng Shen; Muhammad Zaffar Hashmi; Jiyan Shi (Biological Trace Element Research, 2014)

High humidity partially rescues the Arabidopsis thaliana exo70A1 stigmatic defect for accepting compatible pollen - Darya Safavian; Muhammad Jamshed; Subramanian Sankaranarayanan; Emily Indriolo; Marcus A. Samuel; Daphne R. Goring (Plant Reproduction, 2014)

Livelihood diversification as an adaptation approach to change in the pastoral Hindu-Kush Himalayan region - Ning Wu; Muhammad Ismail; Srijana Joshi; Shao-liang Yi; Ritu Meher Shrestha; Abdul Wahid Jasra (Journal of Mountain Science, 2014)

Multi-lineage differentiation of human mesenchymal stromal cells on the biophysical microenvironment of cell-derived matrix - Dong Hoon Choi; Muhammad Suhaeri; Mintai P. Hwang; Ik Hwan Kim; Dong Keun Han; Kwideok Park (Cell and Tissue Research, 2014)

Physiological adaptative characteristics of Imperata cylindrica for salinity tolerance - Mansoor Hameed; Muhammad Ashraf; Nargis Naz; Tahira Nawaz; Riffat Batool; Sana Fatima; Farooq Ahmad (Biologia, 2014)

Sodium and boron exclusion in two Brassica juncea cultivars exposed to the combined treatments of salinity and boron at moderate alkalinity - Muhammad Javid; Rebecca Ford; Robert M. Norton; Marc E. Nicolas (Biologia, 2014)

Shigar valley gemstones, their chemical composition and origin, Skardu, Gilgit-Baltistan, Pakistan - Muhammad Hassan Agheem; Mohammad Tahir Shah; Tahseenullah Khan; Mamoru Murata; Muhammad Arif; Humaira Dars (Arabian Journal of Geosciences, 2014)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)

Pharmacological importance of an ethnobotanical plant: Capsicum annuum L. - Farhan A. Khan; Tariq Mahmood; Muhammad Ali; Abdul Saeed; Aneela Maalik (Natural Product Research, 2014)

Cesium-137: Radio-Chemistry, Fate, and Transport, Remediation, and Future Concerns - Muhammad Aqeel Ashraf; Shatirah Akib; Mohd. Jamil Maah; Ismail Yusoff; Khaled S. Balkhair (Critical Reviews in Environmental Science and Technology, 2014)

Characterization of Reactive Red-120 Decolorizing Bacterial Strain Acinetobacter junii FA10 Capable of Simultaneous Removal of Azo Dyes and Hexavalent Chromium - Faiza Anwar; Sabir Hussain; Shahla Ramzan; Farhan Hafeez; Muhammad Arshad; Muhammad Imran; Zahid Maqbool; Naila Abbas (Water, Air, & Soil Pollution, 2014)

Expression and functional analysis of genes encoding cytokinin receptor-like histidine kinase in maize (Zea mays L.) - Bo Wang; Yanhong Chen; Baojian Guo; Muhammad Rezaul Kabir; Yingyin Yao; Huiru Peng; Chaojie Xie; Yirong Zhang; Qixin Sun; Zhongfu Ni (Molecular Genetics and Genomics, 2014)

Costs of and Investment in Mate-Guarding in Wild Long-Tailed Macaques (Macaca fascicularis): Influences of Female Characteristics and Male–Female Social Bonds - Cédric Girard-Buttoz; Michael Heistermann; Erdiansyah Rahmi; Muhammad Agil; Panji Ahmad Fauzan; Antje Engelhardt (International Journal of Primatology, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

An analysis of the resistance of Gossypium arboreum to cotton leaf curl disease by grafting - Rahim Ullah; Khalid P. Akhtar; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2014)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Development of sustained-release formulations processed by hot-melt extrusion by using a quality-by-design approach - Muhammad T. Islam; Mohammed Maniruzzaman; Sheelagh A. Halsey; Babur Z. Chowdhry; Dennis Douroumis (Drug Delivery and Translational Research, 2014)

A review of the stabilization of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Ahmad Farid Abu Bakar; S. Paramanthan; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2014)

A betasatellite-dependent begomovirus infects ornamental rose: characterization of begomovirus infecting rose in Pakistan - Sandeep Khatri; Nazia Nahid; Claude M. Fauquet; Muhammad Mubin; Muhammad Shah Nawaz-ul-Rehman (Virus Genes, 2014)

Low carbon emission development strategies for Jambi, Indonesia: simulation and trade-off analysis using the FALLOW model - Rachmat Mulia; Atiek Widayati; Suyanto; Putra Agung; Muhammad Thoha Zulkarnain (Mitigation and Adaptation Strategies for Global Change, 2014)

Allelic variation at loci controlling stripe rust resistance in spring wheat - SANIA BEGUM; MUHAMMAD IQBAL; IFTIKHAR AHMED; MUHAMMAD FAYYAZ; ARMGHAN SHAHZAD; GHULAM M. ALI (Journal of Genetics, 2014)

Genetic analysis of a consanguineous Pakistani family with Leber congenital amaurosis identifies a novel mutation in GUCY2D gene - MUZAMMIL AHMAD KHAN; VERENA RUPP; MUHAMMAD AYAZ KHAN; MUHAMMAD PERVAIZ KHAN; MUHAMMAD ANSAR; CHRISTIAN WINDPASSINGER (Journal of Genetics, 2014)

Functional analysis of the venom of mealybug parasitoid Aenasius bambawalei (Hymenoptera: Encyrtidae) - Saqi Kosar Abbas; Zain ul Abdin; Muhammad Jalal Arif; Amer Jamil (Biologia, 2014)

An efficient total synthesis of trilepisiumic acid - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Identification of Quantitative Trait Loci (QTLs) in Aquaculture Species - Muhammad Y. Laghari; Punhal Lashari; Yan Zhang; Xiaowen Sun (Reviews in Fisheries Science & Aquaculture, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Aflatoxin B 1 in betel nuts ( Areca catechu L . ) imported to Pakistan from different regions of South Asia - Muhammad Asif Asghar; Javed Iqbal; Aftab Ahmed; Mobeen Ahmed Khan; Zuzzer Ali Shamsuddin (Food Additives & Contaminants Part B-Surveillance, 2014)

Prediction of leaf nitrogen from early season samples and development of field sampling protocols for nitrogen management in Almond (Prunus dulcis [Mill.] DA Webb) - Sebastian Saa; Patrick H. Brown; Saiful Muhammad; Andres Olivos-Del Rio; Blake L. Sanden; Emilio A. Laca (Plant and Soil, 2014)

Population dynamics of citrus leaf miner on different varieties of citrus in correlation with abiotic environmental factors in Sargodha District, Punjab, Pakistan - Irfan Mustafa; Muhammad Arshad; Abdul Ghani; Iftikhar Ahmad; Abu Bakar Muhammad Raza; Farzana Saddique; Saira Asif; Mobushir Riaz Khan; Haroon Ahmed (Phytoparasitica, 2014)

Mitochondrial Ca2+ uniporter (MCU)-dependent and MCU-independent Ca2+ channels coexist in the inner mitochondrial membrane - Alexander I. Bondarenko; Claire Jean-Quartier; Warisara Parichatikanond; Muhammad Rizwan Alam; Markus Waldeck-Weiermair; Roland Malli; Wolfgang F. Graier (Pflügers Archiv - European Journal of Physiology, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Fluoroquinolones: novel class of gastrointestinal dietary lipid digestion and absorption inhibitors - Yusuf M. Al-Hiari; Violet N. Kasabri; Ashok K. Shakya; Muhammad H. Alzweiri; Fatma U. Afifi; Yasser K. Bustanji; Ihab M. Al-Masri (Medicinal Chemistry Research, 2014)

The Smart 2-(2-Fluorobenzoyl)-N-(2-Methoxyphenyl)Hydrazinecarbothioamide Functionalized as Ni(II) Sensor in Micromolar Concentration Level and its Application in Live Cell Imaging - Muhammad Saleem; Anser Ali; Chang-Shik Choi; Bong Joo Park; Eun Ha Choi; Ki Hwan Lee (Journal of Fluorescence, 2014)

Enhancing Corynebacterium glutamicum robustness by over-expressing a gene, mshA, for mycothiol glycosyltransferase - Ying-Bao Liu; Can Chen; Muhammad Tausif Chaudhry; Mei-Ru Si; Lei Zhang; Yao Wang; Xi-Hui Shen (Biotechnology Letters, 2014)

Description of raabeia, synactinomyxon and neoactinomyxum developing stages of myxosporeans (Myxozoa) infecting Isochaetides michaelseni Lastočkin (Tubificidae) in Lake Balaton and Kis-Balaton Water Reservoir, Hungary - Muhammad Hafiz Borkhanuddin; Gábor Cech; Kálmán Molnár; Sándor Németh; Csaba Székely (Systematic Parasitology, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

New Approach: Integrated Risk-Stochastic Dynamic Model for Dam and Reservoir Optimization - Ahmed El-Shafie; Amr H. El-Shafie; Muhammad Mukhlisin (Water Resources Management, 2014)

QTL for resistance to root lesion nematode (Pratylenchus thornei) from a synthetic hexaploid wheat source - Katherine J. Linsell; Muhammad S. Rahman; Julian D. Taylor; Rowena S. Davey; Beverley J. Gogel; Hugh Wallwork; Kerrie L. Forrest; Matthew J. Hayden; Sharyn P. Taylor; Klaus H. Oldach (Theoretical and Applied Genetics, 2014)

Studies on the role of neutralizing antibodies against envelope genes in resolving HCV pseudo-particles infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Muhammad Iqbal (Molecular Biology Reports, 2014)

Molecular cloning and characterization of a heme oxygenase1 gene from sunflower and its expression profiles in salinity acclimation - Kaikai Zhu; Qijiang Jin; Muhammad Kaleem Samma; Guoqing Lin; Wenbiao Shen (Molecular Biology Reports, 2014)

Generation of infectious HCV pseudo typed particles and its utilization for studying the role of CD81 & SRBI receptors in HCV infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Kashif Iqbal Sahibzada; Muhammad Iqbal (Molecular Biology Reports, 2014)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Silicon Application to Rice Root Zone Influenced the Phytohormonal and Antioxidant Responses Under Salinity Stress - Yoon Ha Kim; Abdul Latif Khan; Muhammad Waqas; Jae Kyoung Shim; Duck Hwan Kim; Kyeong Yeoll Lee; In Jung Lee (Journal of Plant Growth Regulation, 2014)

Regulation of endogenous gibberellins and abscisic acid levels during different seed collection periods in Panax ginseng - Yoon-Ha Kim; In-Ok Ahn; Abdul Latif Khan; Muhammad Kamran; Muhammad Waqas; Joon-Soo Lee; Duk-Hwan Kim; Soo-Won Jang; In-Jung Lee (Horticulture, Environment, and Biotechnology, 2014)

EDTA-enhanced phytoremediation of contaminated calcareous soils: heavy metal bioavailability, extractability, and uptake by maize and sesbania - Vishandas Suthar; Kazi Suleman Memon; Muhammad Mahmood-ul-Hassan (Environmental Monitoring and Assessment, 2014)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Assessment of sulfurous springs in the west of Iraq for balneotherapy, drinking, irrigation and aquaculture purposes - Salih Muhammad Awadh; Sura Abdul Al-Ghani (Environmental Geochemistry and Health, 2014)

Fuzzy synthetic evaluation of treated wastewater reuse for agriculture - Shakhawat Chowdhury; Muhammad Al-Zahrani (Environment, Development and Sustainability, 2014)

Comparative Assessment of Selected Metals in the Scalp Hair and Nails of Lung Cancer Patients and Controls - Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2014)

Emergence of genetically variant Hepatitis C virus population in response to increased antiviral drug pressure, Pakistan - Muhammad Ali; Irshad Ur Rehman; Muhammad Idrees (Virus Genes, 2014)

Petrogenesis of granites from the Utla area of Gadoon, north-west Pakistan: Implications from petrography and geochemistry - Muhammad Sajid; Mohammad Arif; M. Tahir Shah (Journal of Earth Science, 2014)

Bacillus pakistanensis sp. nov., a halotolerant bacterium isolated from salt mines of the Karak Area in Pakistan - Aneela Roohi; Iftikhar Ahmed; Jayoung Paek; Yeseul Sin; Saira Abbas; Muhammad Jamil; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Synergistic effects of drought and ascorbic acid on growth, mineral nutrients and oxidative defense system in canola (Brassica napus L.) plants - Sidra Shafiq; Nudrat Aisha Akram; Muhammad Ashraf; Amara Arshad (Acta Physiologiae Plantarum, 2014)

Biodegradable Injectable In Situ Implants and Microparticles for Sustained Release of Montelukast: In Vitro Release, Pharmacokinetics, and Stability - Tarek A. Ahmed; Hany M. Ibrahim; Ahmed M. Samy; Alaa Kaseem; Mohammad T. H. Nutan; Muhammad Delwar Hussain (AAPS PharmSciTech, 2014)

Integrated effects of organic, inorganic and biological amendments on methane emission, soil quality and rice productivity in irrigated paddy ecosystem of Bangladesh: field study of two consecutive rice growing seasons - Muhammad Aslam Ali; M. A. Sattar; M. Nazmul Islam; K. Inubushi (Plant and Soil, 2014)

Interaction between HY1 and H2O2 in auxin-induced lateral root formation in Arabidopsis - Fei Ma; Lijuan Wang; Jiale Li; Muhammad Kaleem Samma; Yanjie Xie; Ren Wang; Jin Wang; Jing Zhang; Wenbiao Shen (Plant Molecular Biology, 2014)

Recombinant expression and characterization of a novel endoglucanase from Bacillus subtilis in Escherichia coli - Muddassar Zafar; Sibtain Ahmed; Muhammad Imran Mahmood Khan; Amer Jamil (Molecular Biology Reports, 2014)

Evaluation of the thiazole Schiff bases as $$\upbeta $$ β -glucuronidase inhibitors and their in silico studies - Khalid Mohammed Khan; Aneela Karim; Sumayya Saied; Nida Ambreen; Xayale Rustamova; Shagufta Naureen; Sajid Mansoor; Muhammad Ali; Shahnaz Perveen; M. Iqbal Choudhary; Guillermo Antonio Morales (Molecular Diversity, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

Synthesis, characterization antibacterial and antifungal activity of some transition metal complexes - Wajid Rehman; Zonera Hassan; Umer Rashid; Fazal Rahim; Obaid-Ur-Rahman Abid; Muhammad Waseem (Medicinal Chemistry Research, 2014)

Breeding approaches for bacterial leaf blight resistance in rice (Oryza sativa L.), current status and future directions - Mueen Alam Khan; Muhammad Naeem; Muhammad Iqbal (European Journal of Plant Pathology, 2014)

Flowering time in wheat (Triticum aestivum L.): a key factor for global adaptability - Atif Kamran; Muhammad Iqbal; Dean Spaner (Euphytica, 2014)

Does energy consumption contribute to environmental pollutants? evidence from SAARC countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Danish Irfan; Muhammad Mushtaq Khan (Environmental Science and Pollution Research, 2014)

Erratum to: Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Facies analysis and geochemistry of the Euphrates Formation in Central Iraq - Moutaz A. Al-Dabbas; Salih Muhammad Awadh; Ayad Abed Zaid (Arabian Journal of Geosciences, 2014)

A putative poplar PP2C-encoding gene negatively regulates drought and abscisic acid responses in transgenic Arabidopsis thaliana - Muhammad Arshad; Jim Mattsson (Trees, 2014)

Unnoticed but important: revealing the hidden contribution of community-based religious institution of the mosque in disasters - Abdur Rehman Cheema; Regina Scheyvens; Bruce Glavovic; Muhammad Imran (Natural Hazards, 2014)

Identification of recurrent c.742G>T nonsense mutation in ECM1 in Pakistani families suffering from lipoid proteinosis - Muhammad Nasir; Simeen Ber Rahman; Christian M. K. Sieber; Asif Mir; Amir Latif; Nafees Ahmad; Salman Akbar Malik; Abdul Hameed (Molecular Biology Reports, 2014)

Mechanisms of metal-phosphates formation in the rhizosphere soils of pea and tomato: environmental and sanitary consequences - Annabelle Austruy; Muhammad Shahid; Tiantian Xiong; Maryse Castrec; Virginie Payre; Nabeel Khan Niazi; Muhammad Sabir; Camille Dumat (Journal of Soils and Sediments, 2014)

Influence of plant species and phosphorus amendments on metal speciation and bioavailability in a smelter impacted soil: a case study of food-chain contamination - Muhammad Shahid; Tiantian Xiong; Nasir Masood; Tibo Leveque; Katelle Quenea; Annabelle Austruy; Yann Foucault; Camille Dumat (Journal of Soils and Sediments, 2014)

Influence of EDTA and citric acid on lead-induced oxidative stress to Vicia faba roots - Muhammad Shahid; Camille Dumat; Bertrand Pourrut; Jérôme Silvestre; Christophe Laplanche; Eric Pinelli (Journal of Soils and Sediments, 2014)

Accumulation of phlorotannins in the abalone Haliotis discus hannai after feeding the brown seaweed Ecklonia cava - Issa Bangoura; Muhammad Tanvir Hossain Chowdhury; Ji-Young Kang; Ji-Young Cho; Je-Cheon Jun; Yong-Ki Hong (Journal of Applied Phycology, 2014)

Establishing midgut cell culture from Rhynchophorus ferrugineus (Olivier) and toxicity assessment against ten different insecticides - Ahmed Mohammed Aljabr; Muhammad Rizwan-ul-Haq; Abid Hussain; Abdullah I. Al-Mubarak; Hassan Y. AL-Ayied (In Vitro Cellular & Developmental Biology - Animal, 2014)

Assessment of human–leopard conflict in Machiara National Park, Azad Jammu and Kashmir, Pakistan - Muhammad Kabir; Arash Ghoddousi; Muhammad Sadique Awan; Muhammad Naeem Awan (European Journal of Wildlife Research, 2014)

Comparison of understorey bird species in relation to edge–interior gradient in an isolated tropical rainforest of Malaysia - Mohamed Zakaria; Muhammad Nawaz Rajpar; Hossein Varasteh Moradi; Zamri Rosli (Environment, Development and Sustainability, 2014)

Monitoring impacts of air pollution: PIXE analysis and histopathological modalities in evaluating relative risks of elemental contamination - Sohail Ejaz; Gerry Amor Camer; Khaleeq Anwar; Muhammad Ashraf (Ecotoxicology, 2014)

Citric Acid Cycle and Role of its Intermediates in Metabolism - Muhammad Akram (Cell Biochemistry and Biophysics, 2014)

Isolation of Peripheral Blood Mononuclear Cells Using Glycerol Density Gradient - I. A. Aimola; H. M. Inuwa; A. J. Nok; A. I. Mamman; N. Habila; A. Muhammad; U. S. Ndidi; B. Ignatius; P. L. Jande; R. Oghor; L. C. Isaac; N. B. Afolabi-Balogun (Cell Biochemistry and Biophysics, 2014)

Impact of climate change: an empirical investigation of Malaysian rice production - Muhammad Mehedi Masud; Md. Saifur Rahman; Abul Quasem Al-Amin; Fatimah Kari; Walter Leal Filho (Mitigation and Adaptation Strategies for Global Change, 2014)

Mate-guarding constrains feeding activity but not energetic status of wild male long-tailed macaques (Macaca fascicularis) - Cédric Girard-Buttoz; Michael Heistermann; Erdiansyah Rahmi; Anna Marzec; Muhammad Agil; Panji Ahmad Fauzan; Antje Engelhardt (Behavioral Ecology and Sociobiology, 2014)

Factors Affecting the Use of Impedance Spectroscopy in the Characterisation of the Freezing Stage of the Lyophilisation Process: the Impact of Liquid Fill Height in Relation to Electrode Geometry - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina (AAPS PharmSciTech, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Pollen morphology of the genus Euphrasia L. (Orobanchaceae) from Pakistan and Kashmir and its taxonomic significance - Muhammad Qaiser; Anjum Perveen; Tahmeena Siddiqui (Plant Systematics and Evolution, 2014)

Synthetically modified bioisosteres of salicyl alcohol and their gastroulcerogenic assessment versus aspirin: biochemical and histological correlates - Gowhar Ali; Fazal Subhan; Nazar Ul Islam; Nasir Ullah; Robert D. E. Sewell; Muhammad Shahid; Ikhtiar Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

Interleukin-6 inhibition of peroxisome proliferator-activated receptor alpha expression is mediated by JAK2- and PI3K-induced STAT1/3 in HepG2 hepatocyte cells - Guat-Siew Chew; Stephen Myers; Alexander Chong Shu-Chien; Tengku Sifzizul Tengku Muhammad (Molecular and Cellular Biochemistry, 2014)

Antiproliferative effects of novel urea derivatives against human prostate and lung cancer cells; and their inhibition of β-glucuronidase activity - Shahnaz Perveen; Sana Mustafa; Kehkashan Qamar; Ahsana Dar; Khalid M. Khan; Muhammad Iqbal Choudhary; Ajmal Khan; Wolfgang Voelter (Medicinal Chemistry Research, 2014)

MRI and neuropathological validations of the involvement of air pollutants in cortical selective neuronal loss - Sohail Ejaz; Khaleeq Anwar; Muhammad Ashraf (Environmental Science and Pollution Research, 2014)

Induction medium osmolality improves microspore embryogenesis in wheat and triticale - Muhammad Asif; François Eudes; Harpinder Randhawa; Eric Amundsen; Dean Spaner (In Vitro Cellular & Developmental Biology - Plant, 2014)

In vitro propagation of Caralluma tuberculata and evaluation of antioxidant potential - Riaz Ur Rehman; Muhammad Fayyaz Chaudhary; Khalid Mahmood Khawar; Gang Lu; Abdul Mannan; Muhammad Zia (Biologia, 2014)

Directed Evolution of Clostridium phytofermentans Glycoside Hydrolase Family 9 Endoglucanase for Enhanced Specific Activity on Solid Cellulosic Substrate - Sajjad Ahmad; Hui Ma; Muhammad Waheed Akhtar; Yi-Heng Percival Zhang; Xiao-Zhou Zhang (BioEnergy Research, 2014)

Characteristics, modification and environmental application of Yemen’s natural bentonite - Aref Alshameri; Alkhafaji R.Abood; Chunjie Yan; Akhtar Malik Muhammad (Arabian Journal of Geosciences, 2014)

Total synthesis of cytotoxic metabolite ( ± )-desmethyldiaportinol from Ampelomyces sp. - Aamer Saeed; Muhammad Qasim (Natural Product Research, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

Role of heme oxygenase-1 in spermidine-induced alleviation of salt toxicity during alfalfa seed germination - Kaikai Zhu; Jing Zhang; Weiti Cui; Qijiang Jin; Muhammad Kaleem Samma; Wenbiao Shen (Plant and Soil, 2014)

Potential of Bacillus species against Meloidogyne javanica parasitizing eggplant (Solanum melongena L.) and induced biochemical changes - Muhammad Waseem Abbasi; Naeem Ahmed; Muhammad Javed Zaki; S. Shahid Shuakat; D. Khan (Plant and Soil, 2014)

Virus-induced gene silencing for comparative functional studies in Gladiolus hybridus - Xionghui Zhong; Xue Yuan; Ze Wu; Muhammad Ali Khan; Jin Chen; Xiaoxin Li; Benhe Gong; Yang Zhao; Jian Wu; Chenyu Wu; Mingfang Yi (Plant Cell Reports, 2014)

Erratum to: Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Profiling and characterization of eggplant (Solanum melongena L.) microRNAs and their targets - Muhammad Din; Muhammad Younas Khan Barozai (Molecular Biology Reports, 2014)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

Myoloid-Related Protein 8, an Endogenous Ligand of Toll-Like Receptor 4, Is Involved in Epileptogenesis of Mesial Temporal Lobe Epilepsy Via Activation of the Nuclear Factor-κB Pathway in Astrocytes - Na Gan; Lifen Yang; Ahmed Omran; Jing Peng; Liwen Wu; Fang He; Ciliu Zhang; Qiulian Xiang; Huimin Kong; Yupin Ma; Muhammad Usman Ashhab; Xiaolu Deng; et al. (Molecular Neurobiology, 2014)

POM analyses of antimicrobial activity of some 2,3-armed 4,5,6,7-tetrahydro-1-benzothiophenes: favourable and unfavourable physico-chemical parameters in design of antibacterial and mycolytic agents - Taibi Ben Hadda; Sajal Srivastava; Barnali Das; Héctor Salgado-Zamora; Usama Shaheen; Ammar Bader; Muhammad Moazzam Naseer (Medicinal Chemistry Research, 2014)

Fast bioassessment of wastewater and surface water quality using freshwater flagellate Euglena gracilis—a case study from Pakistan - Azizullah Azizullah; Muhammad Jamil; Peter Richter; Donat-Peter Häder (Journal of Applied Phycology, 2014)

New sources of resistance to Phytophthora capsici in Capsicum spp. - Hwangsung Mo; Soyoung Kim; Khin Pa Pa Wai; Muhammad Irfan Siddique; Heeju Yoo; Byung-Soo Kim (Horticulture, Environment, and Biotechnology, 2014)

Assessment of Toxicity and Potential Risk of Butene-fipronil Using Drosophila melanogaster, in Comparison to Nine Conventional Insecticides - Muhammad Shahid Arain; Xing-Xing Hu; Guo-Qing Li (Bulletin of Environmental Contamination and Toxicology, 2014)

HCN production and hydroxynitrile lyase: a natural activity in plants and a renewed biotechnological interest - Muhammad Arshad Kassim; Karl Rumbold (Biotechnology Letters, 2014)

The endophyte Enterobacter sp. FD17: a maize growth enhancer selected based on rigorous testing of plant beneficial traits and colonization characteristics - Muhammad Naveed; Birgit Mitter; Sohail Yousaf; Milica Pastar; Muhammad Afzal; Angela Sessitsch (Biology and Fertility of Soils, 2014)

Large scale mass movements triggered by the Kashmir earthquake 2005, Pakistan - Muhammad Basharat; Joachim Rohn; Mirza Shahid Baig; Muhammad Rustam Khan; Markus Schleier (Journal of Mountain Science, 2014)

Detection of New Point Mutations of BRCA1 and BRCA2 in Breast Cancer Patients - Moufida Bensam; Elsayed Hafez; Doaa Awad; Muhammad El-Saadani; Mahmoud Balbaa (Biochemical Genetics, 2014)

A study of aerosol properties over Lahore (Pakistan) by using AERONET data - Muhammad Ali; Salman Tariq; Khalid Mahmood; Asim Daud; Adila Batool; Zia-ul-Haq (Asia-Pacific Journal of Atmospheric Sciences, 2014)

Erratum to: Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Augmenting drought tolerance in sorghum by silicon nutrition - Mukhtar Ahmed; Muhammad Asif; Fayyaz-ul Hassan (Acta Physiologiae Plantarum, 2014)

Antioxidant response of Cassia angustifolia Vahl. to oxidative stress caused by Mancozeb, a pyrethroid fungicide - Uzma Majid; Mahmooduzzafar; Tariq Omar Siddiqi; Muhammad Iqbal (Acta Physiologiae Plantarum, 2014)

Inferring the contribution of sexual reproduction, migration and off‐season survival to the temporal maintenance of microbial populations: a case study on the wheat fungal pathogen P uccinia striiformis f.sp. tritici - Sajid Ali; Pierre Gladieux; Hidayatur Rahman; Muhammad S. Saqib; Muhammad Fiaz; Habib Ahmad; Marc Leconte; Angélique Gautier; Annemarie F. Justesen; Mogens S. Hovmøller; Jérôme Enjalbert; Claude de Vallavieille‐Pope (Molecular Ecology, 2014)
Understanding the mode of temporal maintenance of plant pathogens is an important domain of microbial ecology research. Due to the inconspicuous nature of microbes, their temporal maintenance cannot be studied directly through tracking individuals and their progeny. Here, we suggest a series of population genetic analyses on molecular marker variation in temporally spaced samples to infer about the relative contribution of sexual reproduction, off‐season survival and migration to the temporal maintenance of pathogen populations. We used the proposed approach to investigate the temporal maintenance of wheat yellow rust pathogen, P uccinia striiformis f.sp. tritici ( PST ), in the H imalayan region of P akistan. Multilocus microsatellite genotyping of PST isolates revealed high genotypic diversity and recombinant population structure across all locations, confirming the existence of sexual reproduction in this region. The genotypes were assigned to four genetic groups, revealing a clear differentiation between zones with and without B erberis spp., the alternate host of PST , with an additional subdivision within the B erberis zone. The lack of any differentiation between samples across two sampling years, and the very infrequent resampling of multilocus genotypes over years at a given location was consistent with limited over‐year clonal survival, and a limited genetic drift. The off‐season oversummering population in the B erberis zone, likely to be maintained locally, served as a source of migrants contributing to the temporal maintenance in the non‐ B erberis zone. Our study hence demonstrated the contribution of both sexual recombination and off‐season oversummering survival to the temporal maintenance of the pathogen. These new insights into the population biology of PST highlight the general usefulness of the analytical approach proposed.

Aflatoxin M 1 in milk from urban and rural farmhouses of Punjab, Pakistan - Shahzad Zafar Iqbal; Muhammad Rafique Asi; Jinap Selamat (Food Additives & Contaminants Part B-Surveillance, 2014)

Aflatoxins contamination and prevention in red chillies ( Capsicum annuum L. ) in Pakistan - Mobeen Ahmed Khan; Muhammad Asif Asghar; Javed Iqbal; Aftab Ahmed; Zuzzer Ali Shamsuddin (Food Additives & Contaminants Part B-Surveillance, 2014)

A Question Mark on Zinc Deficiency in 185 Million People in Pakistan—Possible Way Out - Nauman Khalid; Anwaar Ahmed; Muhammad Shahbaz Bhatti; Muhammad Atif Randhawa; Asif Ahmad; Rabab Rafaqat (Critical Reviews in Food Science and Nutrition, 2014)

Cheddar Cheese Ripening and Flavor Characterization: A Review - Mian Anjum Murtaza; Salim Ur-Rehman; Faqir Muhammad Anjum; Nuzhat Huma; Iram Hafiz (Critical Reviews in Food Science and Nutrition, 2014)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

Perspective of Surface Active Agents in Baking Industry: An Overview - Asif Ahmad; Nazish Arshad; Zaheer Ahmed; Muhammad Shahbaz Bhatti; Tahir Zahoor; Nomana Anjum; Hajra Ahmad; Asma Afreen (Critical Reviews in Food Science and Nutrition, 2014)

Erratum to: Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2014)

Association mapping of six yield-related traits in rapeseed (Brassica napus L.) - Dongfang Cai; Yingjie Xiao; Wei Yang; Wei Ye; Bo Wang; Muhammad Younas; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2014)

Effects of drought and elevated temperature on biochemical composition of forage plants and their impact on carbon storage in grassland soil - Muhammad Sanaullah; Abad Chabbi; Cyril Girardin; Jean-Louis Durand; Magalie Poirier; Cornelia Rumpel (Plant and Soil, 2014)

Soil organic C and nutrient contents under trees with different functional characteristics in seasonally dry tropical silvopastures - Pere Casals; Johanna Romero; Graciela M. Rusch; Muhammad Ibrahim (Plant and Soil, 2014)

Phytosulfokine alpha enhances microspore embryogenesis in both triticale and wheat - Muhammad Asif; François Eudes; Harpinder Randhawa; Eric Amundsen; Dean Spaner (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Interactions of ketoamide inhibitors on HCV NS3/4A protease target: molecular docking studies - Abdul Wadood; Muhammad Riaz; Syed Babar Jamal; Masaud Shah (Molecular Biology Reports, 2014)

Therapeutic exploration of betulinic acid in chemically induced hypothyroidism - Muhammad Afzal; Imran Kazmi; Susmita Semwal; Fahad A. Al-Abbasi; Firoz Anwar (Molecular and Cellular Biochemistry, 2014)

The potential of the flora from different regions of Pakistan in phytoremediation: a review - Muhammad Aqeel Kamran; Amna; Rabia Mufti; Nadia Mubariz; Jabir Hussain Syed; Asghari Bano; Muhammad Tariq Javed; Muhammad Farooq Hussain Munis; Zhiyuan Tan; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2014)

Heavy metal accumulation in edible fish species from Rawal Lake Reservoir, Pakistan - Riffat Naseem Malik; Muhammad Zaffar Hashmi; Yasmin Huma (Environmental Science and Pollution Research, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

Aquatic biomonitoring of Giardia cysts and Cryptosporidium oocysts in peninsular Malaysia - Soo Ching Lee; Romano Ngui; Tiong Kai Tan; Muhammad Aidil Roslan; Init Ithoi; Yvonne AL Lim (Environmental Science and Pollution Research, 2014)

A rapid and cost-effective method of producing recombinant proBNP and NT-proBNP variants in Escherichia coli for immunoassay of heart failure - Muhammad Tarmizi Soleh; Jared Yong Yang Foo; Ulla-Maja Bailey; Nikki Yi Tan; Yunxia Wan; Justin Cooper-White; Benjamin Luke Schulz; Chamindie Punyadeera (Biotechnology Letters, 2014)

Fungal endophyte Penicillium janthinellum LK5 can reduce cadmium toxicity in Solanum lycopersicum (Sitiens and Rhe) - Abdul Latif Khan; Muhammad Waqas; Javid Hussain; Ahmed Al-Harrasi; In-Jung Lee (Biology and Fertility of Soils, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

A suggested classification for two groups of Campylobacter myoviruses - Muhammad Afzal Javed; Hans-Wolfgang Ackermann; Joana Azeredo; Carla M. Carvalho; Ian Connerton; Stephane Evoy; Jens André Hammerl; Stefan Hertwig; Rob Lavigne; Amit Singh; Christine M. Szymanski; Andrew Timms; et al. (Archives of Virology, 2014)

Deciphering the role of Burkholderia cenocepacia membrane proteins in antimicrobial properties of chitosan - Muhammad Ibrahim; Zhongyun Tao; Annam Hussain; Yang Chunlan; Mehmoona Ilyas; Abdul Waheed; Fang Yuan; Bin Li; Guan-Lin Xie (Archives of Microbiology, 2014)

Heavy-Metal Levels in Feathers of Cattle Egret and Their Surrounding Environment: A Case of the Punjab Province, Pakistan - Kaleem Ullah; Muhammad Zaffar Hashmi; Riffat Naseem Malik (Archives of Environmental Contamination and Toxicology, 2014)

Integrated stratigraphy and palaeoenvironment of the P/E boundary interval, Rakhi Nala section, Indus Basin (Pakistan) - Muhammad Hanif; Malcolm B. Hart; Stephen T. Grimes; Melanie J. Leng (Arabian Journal of Geosciences, 2014)

Effect of heavy metal pollution on mineral absorption in sunflower (Helianthus annuus L.) hybrids - Unaiza Aslam; Iftikhar Ahmad; Mumtaz Hussain; Ameer Khan; Abdul Ghani; Irfan Mustafa; Sabahat Jalal; Muhammad Anjum Aqeel; Saira Asif; Haroon Ahmed (Acta Physiologiae Plantarum, 2014)